Explorando os fractais para o desenvolvimento das habilidades relacionadas ao ensino de álgebra no 7º ano do ensino fundamental - Oliveira, Leonardo Gondim de (2022)
Faced with the difficulties of learning the content and understanding of mathematical concepts and more specifically the difficulties of understanding algebra in the seventh year of elementary school, we seek to develop activities that allow the introduction and deepening of essential concepts for learning algebra and for the development of algebraic thinking in a contextualized way, privileging the processes of investigation, problem solving and modeling. We found in the beauty and characteristics of fractals a support for the development of these activities. Thus, the purpose of this is to suggest investigation and problem solving activities based on the exploration of the Triminó, Koch Curve and Pythagorean Tree fractals that allow the introduction of concepts and the development of skills related to the thematic unit algebra in line with the BNCC.